Investment tax incentives and their big time-to-build fiscal multiplier - Dimitrios Bermperoglou; Yota Deli; Sarantis Kalyvitis (University College Dublin, UCD School of Economics, 2022)
This paper studies how investment tax incentives stimulate output in an estimated medium-scale dynamic stochastic general equilibrium model. We find that the horizon following a positive shock to investment tax incentives is crucial. The shock is highly expansionary in the long run, with the relevant fiscal multiplier substantially exceeding 1, but this effect only becomes visible after two to three years. Anticipation does matter with output being adversely affected before the materialization of the shock yielding a fiscal multiplier above 1 in the long run.
Keywords: E32; E62; H29; 330; investment tax credit; fiscal policy; fiscal multiplier